Research Performance of Turkish Economists and Economics Departments: Another Update and a Review of the 2000s - (:unkn) unknown (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2019)
This article discusses publication performance and patterns of Turkish economists by analyzing changes overtime and comparing results to economists' performance in some emerging economies. The results indicate that (1) the publication performance of Turkish economists and economics departments has improved rapidly over the years but they are still performing below their potential; (2) there is a remarkable difference in research performance among the institutions, but competition has been increasing; (3) the majority of contributions to research output in Turkey are made by six leading universities, but competitive pressure is coming from other institutions; (4) the faculties of the six leading universities are highly motivated to publish in high-quality journals, while members of the other institutions are also increasingly eager to find themselves a place in these outlets; (5) more than one-third of the articles are published in 10 of the 350 Social Sciences Citation Index (SSCI) Economics Journals, but the concentration ratio is decreasing overtime; (6) publication performance and patterns of Turkish economists are similar to their counterparts in emerging economies, but in some aspects Turkish economists perform better.
Keywords: economics departments; economists; publication incentives; publication performance; Turkey; ACADEMIC JOURNALS; RANKINGS; PUBLICATIONS; PRODUCTIVITY; INSTITUTIONS